First Century Christian Diversity Historical Evidence of a Social Phenomenon - Lingelbach, John F. (2019)
In light of Ken Howard’s recent “religion singularity” phenomenon, this article attempts to ascertain the nature of Christian diversity during the last seventy years of the first century (roughly 30 to 100 CE). It offers an examination of the two largest Christian movements that existed before the second century, as well as when those movements may have begun and the locations they most likely flourished. The article argues that the earliest Christian tradition was the one persecuted by the Apostle Paul and that later, two breakaway movements splintered off from this tradition: the Pauline and Ebionite movements. The paper concludes that during the first century, of these two splinter movements, the Pauline movement likely preceded that of the Ebionite movement, though they both flourished in many of the same locations. Of interest is the finding that all three Christian movements (the pre-Pauline tradition, Pauline, and Ebionite) flourished in Asia Minor, a cosmopolitan sub-continent which appears to have served as a geographic information nucleus through which diverse ideas easily proliferated.